Respuesta :
The answer is -25+10x-x^2
-(5-x)^2
-(25-10x+x^2)
-25+10x-x^2
Hope I helped! :)
-(5-x)^2
-(25-10x+x^2)
-25+10x-x^2
Hope I helped! :)
Simple....
you have: [tex]-(5- x)^{2} [/tex]
(The negative you have in front of this is either not supposed to be here or it's trying to trick you..)
[tex]-(5- x)^{2} [/tex]
Substitute the (-) into the equation-->>>
[tex](-5+ x)^{2} [/tex]
or
[tex](x-5)^{2} [/tex]
And then this turns into a very understandable math problem-->>
x*x= [tex] x^{2} [/tex]
-5*x= -5x
-5*x= -5x
-5*-5= 25
Now we add it all up-->>>
[tex] x^{2} [/tex]-10x+25
Thus, your answer.
you have: [tex]-(5- x)^{2} [/tex]
(The negative you have in front of this is either not supposed to be here or it's trying to trick you..)
[tex]-(5- x)^{2} [/tex]
Substitute the (-) into the equation-->>>
[tex](-5+ x)^{2} [/tex]
or
[tex](x-5)^{2} [/tex]
And then this turns into a very understandable math problem-->>
x*x= [tex] x^{2} [/tex]
-5*x= -5x
-5*x= -5x
-5*-5= 25
Now we add it all up-->>>
[tex] x^{2} [/tex]-10x+25
Thus, your answer.